2019
DOI: 10.31486/toj.18.0114
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Current Management Practices for Carotid Webs

Abstract: Background: Carotid webs are thick, fibrous intimal bands that appear as intraluminal shelf-like defects at the carotid bifurcation on vascular imaging. These lesions are a potential underrecognized cause of cryptogenic ischemic stroke. Although the recognition of carotid webs has increased, no evidence-based treatment guidelines are available. We surveyed subspecialists across multiple neurologic disciplines to assess the state of current clinical practice.Methods: An 8-question multiple-choice style survey o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…Our study showed that the diagnosis of CaW was highly underestimated as we considered the causes of ischemic strokes. It corresponds to Wojcik’s reports, which clearly show that familiarity with this clinical problem varies significantly between different specializations; however, generally, the knowledge about this pathology is low [ 14 ].…”
Section: Discussionsupporting
confidence: 81%
“…Our study showed that the diagnosis of CaW was highly underestimated as we considered the causes of ischemic strokes. It corresponds to Wojcik’s reports, which clearly show that familiarity with this clinical problem varies significantly between different specializations; however, generally, the knowledge about this pathology is low [ 14 ].…”
Section: Discussionsupporting
confidence: 81%
“…Although no randomized data are available, invasive treatment such as surgery or stenting seems now increasingly proposed as secondary preventive strategy. 29 In the present study, patients treated with surgery or stenting had a higher rate of vessel occlusion and a more severe stenosis related to CaW than medically treated patients. Physicians and patients may have been more convinced that CaW was responsible for CIE when the lesion was more prominent and associated with artery occlusion.…”
Section: Discussionmentioning
confidence: 43%
“…CTA is the most commonly used method to diagnose a carotid web because the image can be reconstructed in multiple planes, and the contrast image identifies any thrombus associated with the carotid web 17 (Figure 1). Additionally, CTA provides high spatial density resolution images to evaluate for underlying atherosclerotic plaques or cholesterol deposits.…”
Section: Discussionmentioning
confidence: 99%